2018
DOI: 10.1007/s00520-018-4249-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of PCT and IL-6 for bacterial infection in children with cancer and febrile neutropenia

Abstract: PurposeOnly a third of children with cancer and febrile neutropenia (FN) have a proven bacterial infection; nevertheless, most children are hospitalized and treated with intravenous antibiotics. Several biomarkers have been proposed as predictive markers for bacterial infection in this population. We aimed to evaluate the role of interleukin-6 (IL-6) and procalcitonin (PCT) in diagnosing bacterial infection in children with cancer and FN.MethodsThe study population was derived from a prospective database (2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Thirteen studies in this review used more than one biomarker and gave comparative descriptions of performance . Three out of the four studies comparing the performance of CRP and PCT found the latter to be better at predicting adverse outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies in this review used more than one biomarker and gave comparative descriptions of performance . Three out of the four studies comparing the performance of CRP and PCT found the latter to be better at predicting adverse outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies explored the predictive role of IL‐6 and IL‐8: one found IL8 to perform better, one found them to be equivalent, and the other three did not make any comparisons . There were no direct comparisons of PCT with IL‐8 but one study compared the predictive value of PCT to IL‐6, finding that IL‐6 demonstrated better discriminatory power at admission and at 12‐24 h of admission but particularly at admission. The authors also found combining PCT (>0.25 ng/L) with IL‐6 (>60 ng/L), which significantly increased the likelihood of identifying a bacterial infection at both time points.…”
Section: Resultsmentioning
confidence: 99%
“…Klebsiella pneumoniae stands as one of the most prevalent pathogens among cancer patients and a major complication among those undergoing chemotherapy, with infection and mortality rates due to bacteremia ranging from 10% to 53% and 18% to 30%, respectively [ 1 , 2 , 3 , 4 ]. Worryingly, mortality rates reaching 72.7% have been reported due to the spread of multidrug-resistant (MDR) and carbapenemase-producing K. pneumoniae strains [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe and prolonged neutropenia induced by chemotherapy is the main risk factor for the acquisition of serious infections, including those caused by MDR pathogens [ 10 , 11 ]. Moreover, immunocompromised individuals demonstrate few clinical signs in bacterial infections, which are commonly confused with the symptoms of the underlying neoplasm or treatment side effects [ 7 , 10 , 11 ]. Other risk factors that contribute to poor prognosis infections in cancer patients are myeloablative therapy, total body irradiation, high doses of steroids, tissue grafting, prolonged hospitalization, recent surgery, resection of multiple organs, exposed cancer, enteral diet, ostomies, admission to intensive care unit (ICUs), presence of central venous catheter, bladder catheterization, ventilatory assistance, hemodialysis and disease chronic pulmonary disease [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the immune system they modulate the balance between humoral and cellular responses. Elevated serum cytokines have also been studied in febrile illnesses associated, or not, with infectious diseases but without direct comparison with KD ( van der Galien et al, 2018 , Chandrashekara et al, 2016 , Zheng et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%